Inputs, Gender Roles or Sharing Norms? Assessing the Gender Performance Gap Among Informal Entrepreneurs in Madagascar - Christophe Jalil Nordman; Julia Vaillant (Institute for the Study of Labor (IZA), 2014)
We use a representative sample of informal entrepreneurs in Madagascar to add new evidence on the magnitude of the gender performance gap. After controlling for business and entrepreneur characteristics, female-owned businesses exhibit a value added 28 percent lower than their male counterparts. Correcting for endogenous selection into informal self-employment raises the gap by 5 percentage points. We then investigate the role of sharing norms and gender-differentiated allocation of time within the household in the gender performance gap, by estimating their effect on the technical inefficiency of female and male entrepreneurs. Only male entrepreneurs seem subject to pressure to redistribute from the distant network. Our findings are consistent with situations where women working at home would essentially feel negatively the burden of their own community due to intense social norms and obligations in their workplace but also of domestic chores and responsibilities. We find evidence of females self-selecting themselves into industries in which they can combine market-oriented and domestic activities.
Keywords: D13; D61; O12; J16; 330; gender; entrepreneurship; informal sector; sharing norms; household composition; Madagascar